2013
DOI: 10.1111/trf.12072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of various blood and graft sources: a prospective series

Abstract: Our study shows strong differences in terms of quantitative and qualitative cellular composition between several blood or graft sources, possibly explaining the differences observed in terms of outcomes after transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In line with our findings, Rodriguez-Cortes et al describe an extensive increase of leukocytes after G-CSF mobilization, including a moderate increase of lymphocytes [ 15 ]. Our observations are also consistent with data from Chevallier et al [ 16 ] and Sica et al [ 17 ].
Fig.
…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In line with our findings, Rodriguez-Cortes et al describe an extensive increase of leukocytes after G-CSF mobilization, including a moderate increase of lymphocytes [ 15 ]. Our observations are also consistent with data from Chevallier et al [ 16 ] and Sica et al [ 17 ].
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…Nawa et al [ 39 ] described a reduced stimulatory potential of monocytes from G-CSF mobilized donors in mixed lymphocyte reactions, potentially indicating reduced potential of such monocytes to stimulate T-cell responses; however, they described that T-cell function was not directly altered by G-CSF mobilization. Others described that the cell count of dendritic cells per µl PB is increased after mobilization [ 15 , 16 ] bearing the advantage that these dendritic cells as APCs may contribute to effective expansion of antigen-specific T cells in protocols such as ours. During our cultivation process, however, G-CSF is absent, and we observed that 9-day cultures from G-CSF mobilized donors resulted in equal relative expansion of virus-specific T cells in comparison to cultures from non-mobilized donors, and T-cell function, as measured in ELISpot, was even better for mobilized donors.…”
Section: Discussionmentioning
confidence: 99%
“…BM contains larger volume, more red blood cells, but less white blood cells and HSCs as compared to PBSC (38). Due to the large amounts of red blood cells in BM, ABO mismatch between donor and recipient have to be considered.…”
Section: Different Types Of Hsct Graftsmentioning
confidence: 99%
“…BMT, bone marrow transplantation; CBT, cord blood transplantation; cGVHD, chronic graft-versus-host disease; CI, confidence interval; HCT, haematopoietic cell transplantation; IST, immunosuppressive treatment; PBSCT, peripheral blood stem cell transplantation; TSCM, T memory stem cells. blood grafts compared to those in bone marrow and granulocyte colony-stimulating factor-mobilized peripheral blood grafts for HCT (Chevallier et al, 2013). In fact, TSCMs were found at very low levels in cord blood (Gattinoni et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…These findings observed in CBT were not consistent with previous studies, which suggested that CD4 + T cell reconstitution after CBT with ATG (Jacobson et al , ; Bejanyan et al , ) or without ATG (Kanda et al , ) was delayed compared to allogeneic HCT from other graft sources. Given that the T‐cell receptor rearrangement excision circles (TREC) were of a low copy number in TSCMs compared with TNs (Gattinoni et al , ), the higher proportion of CD4 + TSCMs early after CBT may be partly due to significantly higher proportions of TNs and CD4 + T cells in cord blood grafts compared to those in bone marrow and granulocyte colony‐stimulating factor‐mobilized peripheral blood grafts for HCT (Chevallier et al , ). In fact, TSCMs were found at very low levels in cord blood (Gattinoni et al , ).…”
Section: Discussionmentioning
confidence: 99%